Mannose-centered aromatic galactoclusters inhibit the biofilm formation of Pseudomonas aeruginosa1. Issue 31 (21st August 2015) - Ligeour, Caroline; Vidal, Olivier; Dupin, Lucie; Casoni, Francesca; Gillon, Emilie; Meyer, Albert; Vidal, Sébastien; Vergoten, Gérard; Lacroix, Jean-Marie; Souteyrand, Eliane; Imberty, Anne; Vasseur, Jean-Jacques; et al.
<x xml:space="preserve">Abstract</x> Two galactosylated glycoclusters show high affinity for LecA from Pseudomonas aeruginosa and anti-biofilm activity.